Avaliação da nitrificação de efluente de abatedouro de tilápia em reator em batelada seqüencial aerado com biomassa imobilizada - Zenatti, Dilcemara Cristina (2007)
The agribusiness possesses a high potential of negative environmental impacts related to the generation of residues, overcoat of liquid effluents rich in organic matter and nutrients. The release of those no treated effluents has been the cause of serious damages to the environment. The biological treatment of the nitrogen compositions has been an alternative to improve the quality of the effluents. One of the biological processes is constituted of the nitrification follow by desnitrification, being the nitrification the limiting factor for good performance of the system. The objective of this work was to evaluate the influence of the aeration and of the time of reaction in the process of nitrification of the tilapia effluent in sequential batch reactor with immobilized biomass. The experiment was driven in laboratory scale where two levels of flow of air were tested (QAr = 3 and 6 L.min-1) and two levels of time of reaction (TR = 6 and 12 hours), configuring a factorial experimental planned with four treatments: T1 (QAr=3 L.min-1 and TR = 6:00); T2 (QAr=6 L.min-1 and TR = 6:00), T3 (QAr=3 L.min- 1 and TR = 12:00) and T1 (QAr=6 L.min-1 and TR = 12:00), and four repetitions. The efficiency of Conversion was evaluated (%) of the amoniacal nitrogen to nitrate, the efficiency of Removal (%) of amoniacal nitrogen and the kinetic profile of the nitrification, with the calculation of the apparent kinetic constants k1 and k2. The results showed that the increase in the reaction time (TR) and the increment in the air flow is favorable in the nitrification process. Being that the T4 treatment was what presented better resulted in all the factors analyzed with average values of efficiency for conversion and removal of 57,27± 27,05% and 81,90±3,80, respectively and 0,00300±0,00030 min-1 and 0,00298±0,00024 min-1 for the apparent constants k1 and k2.